The large-scale economic and industrial systems structural and organizational sustainability ensuring through enterprise engineering methodology - Shmatko, Nataliia (Sp. z o.o. "Nauka i studia", 2018)
In the new global economy enterprise integration and collaboration has become a central issue for achieving the market success, which is why the significant amount of the large-scale enterprise and industrial systems (LSEIS) has appeared. Despite LSEIS efficacy, their participants suffer from several major drawbacks: the limited rationality and opportunistic behavior from other LSEIS participants, the insufficient coordination because of the possibility of setting the different goals than consolidated LSEIS vision. All these deficiencies lead LSEIS towards to losing the stability of functioning and require developing the approach for its avoiding. Given this, this article aims to propose the conceptual, theoretical framework for the ensuring the structural and organizational sustainability of LSEIS functioning. The achieving of this aims based on the author’s hypothesis about the ensuring LSEIS sustainability through the optimization of the LSEIS participants’ interaction parameters and establishing the set of business rules accepted by all members of an integrated organization. In order to prove this hypothesis was used the DEMO (Design and Engineering Methodology for Organizations) methodology.
Keywords: design methodology; engineering methodology; organization; industrial system; enterprise interaction; enterprise ontology; structural sustainability; organizational sustainability; enterprise engineering